Carbon and Nitrogen Cycle Dynamic in Continental Late-Carboniferous to Early Permian Basins of Eastern Pangea (Northeastern Massif Central, France) - Mercuzot, Mathilde; Thomazo, Christophe; Schnyder, Johann; Pellenard, Pierre; Baudin, François; Pierson-Wickmann, Anne-Catherine; Sans-Jofre, Pierre; Bourquin, Sylvie; Beccaletto, Laurent; Santoni, Anne-Lise; Gand, Georges; Buisson, Matthieu; et al. (Frontiers in Earth Science, 2021)
Late Carboniferous to early Permian organic-rich sedimentary successions of late-orogenic continental basins from the northeastern Massif Central (France) coincide with both the Variscan mountain dismantling and the acme of the long-lasting Late Paleozoic Ice Age. Here, we investigate the carbon and nitrogen cycles in the newly dated sedimentary successions of the Decize–La Machine and Autun basins during these geodynamic and climate upheavals. The sedimentary organic matter has been analysed through Rock-Eval pyrolysis, palynofacies and elemental and isotope geochemistry along cored-wells and outcropping sections, previously accurately defined in terms of paleo-depositional environments. Rock-Eval and palynofacies data have evidenced two origins of organic matter: a phytoplanktonic/bacterial lacustrine origin (Type I organic matter, organic δ13C values around -23.5‰), and a terrestrial origin (vascular land plants, Type III organic matter, organic δ13C values around -20‰), mixed in the deltaic-lacustrine sediments during background sedimentation (mean organic δ13C values around -22‰). Episodes of high organic matter storage, reflected by black shales and coal-bearing deposits (total organic carbon up to 20% and 70%, respectively) are also recognized in the successions, and are characterized by large negative organic carbon isotope excursions down to -29‰. We suggest that these negative isotope excursions reflect secondary processes, such as organic matter remineralization and/or secondary productivity varying under strict local controls, or possibly larger scale climate controls. At times, these negative δ13C excursions are paired with positive δ15N excursions up to +10‰, reflecting water column denitrification and anammox during lake-water stratification episodes. Together, these isotopic signals (i.e., low sedimentary organic δ13C associated with high bulk δ15N values) indicate periods of high primary productivity of surface waters, where nitrogen and carbon cycles are spatially decoupled. These local processes on the sedimentary isotope archives may partially blur our ability to directly reconstruct paleoclimate variations in such continental settings using only C and N isotopes. At last, we explore an organic δ13C-based mixing model to propose ways to disentangle autochthonous versus allochthonous origin of organic matter in lacustrine continental settings.